Urgensi Pembentukan Daerah Otonomi Baru (DOB) di Jawa Barat - Suwari Akhmaddhian; Haris Budiman; Iman Jalaludin Rifa’i; Gilang Ramadhan; Erga Yuhandra (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
The purpose of writing this paper is to find out how to regulate the authority of the Regional Representatives Council and to find out the obstacles of the Regional Representative Council in carrying out the Formation and Expansion of Regions in West Java Province. The method used in this study is an empirical juridical approach using primary and secondary data and data collection techniques used through interviews, observations and literature studies. The result of this research is the regulation on the authority of the Regional Representatives Council based on Article 22 D of the 1945 Constitution of the Republic of Indonesia and Government Regulation Number 78 of 2007 concerning Procedures for the Establishment, Abolition and Merger of Regions, the implementation of these regulations has been in accordance with the existence of a new autonomous region candidate. An effort to equalize public services, it's just that the regulation of the authority of the Regional Representatives Council is strengthened so that it is more capable of carrying out legislative functions for the benefit of the region, as well as obstacles to the Regional Representative Council starting from the absence of approval of the new regional head candidate to the last moratorium. The conclusion of this research is that the regulation of the Regional Representatives Council Authority has not provided a balance in the constitutional system because of the imbalance between the Regional Representatives Council and the People's Representative Council in the legislative function in parliament and the Regional Representative Council still has obstacles in carrying out regional expansion. As the suggetion of this research is that it needs a regulation that clearly regulates the authority of the Regional Representatives Council in the State Administration system in Indonesia so that the Regional Representative Council is more capable of carrying out legislative functions for the benefit of the region, as well as regulations or rules regarding the Formation and Expansion of Regions should have legal certainty dimensions so that they are not ambiguous in regarding the implementation of Regional Formation and Expansion.